Adoption of common bean technologies and its impacts on productivity and household welfare in Ethiopia: Lessons from tropical legumes project - Habte, Endeshaw; Katungi, Enid; Yirga, Chilot; Berhanu, Amsalu; Ratz, Bodo; Mukankusi, Clare; Rubyogo, Jean-Claude; Sebatta, Christopher (Ethiopian Institute of Agricultural Research, 2021)
This report presents adoption patterns of common bean varieties with associated technologies and the resultant effects on productivity and household well-being. In a bid to identify the key variables that govern the use of the technologies promoted by the project, on the one hand, and to examine the impact of the technologies adopted on the livelihood and productivity of bean farmers, on the other, appropriate statistical and econometric techniques were employed. The findings and the conclusions drawn thereof are assumed to represent features of common bean growers in the country. The recommendations are of paramount importance in informing the breeding program and seed system of common bean in the country. importance in informing the breeding program and seed system of common bean in the country.